Hubungan Antara Frekuensi Menyikat Gigi, Cara Menyikat Gigi dan Kebiasaan Makan dengan Kejadian Karies - Winarto Putri, Windi; Nina (MPI Press, 2021)
Introduction: Dental caries are experienced by all circles of thecommunity, ranging from adults, adolescent age groups, to childrenof both men and women. Children between 6-12 years of age aremore prone to dental diseases such as caries often consume fastfood or sweet snacks, at that age there is a change in tooth growthfrom the oldest tooth into adult or permanent teeth. Objectives: This research aims to know the relationship betweenthe frequency of teeth brushing, how to brush teeth and eatinghabits with the incidence of Karies in elementary school students inthe work Area Health District Kemang Bogor Year 2019Method: The design of this research is descriptive analytic to learnthe causal relationship between the two variables in a situation ora group of subjects conducted to see the relationship between onevariable and the other the approach used In this research is crosssectional. The population of this study is the primary schoolstudents of MI Al Islamiyah, MI Al Fitriyah, SDN Pabuaran 01,SDN Bojong 02 with a population of 151 students. Determinationof the sample using Slovin method with sample sampling usingsimple random sampling, obtained as much as 110 respondents.Data retrieval using questionnaires, then processed and analyzedunivariate and bivariate.Result: The results of the analysis showed that there is arelationship frequency tooth brushing (p-value = 0.000), How tobrush teeth (P-value = 0.000), and eating habits (p-value = 0,000)with Genesis Karies on elementary School students in the work areaPuskesmas Kemang Bogor District Year 2019. The child willemulate the behavior of his parents, so the parents are expected toknow how to brush good teeth and correct Conclution: The child will emulate the behavior of his parents, sothe parents are expected to know how to brush good teeth andcorrect